J.R.R. Tolkien's sanctifying myth : understanding Middle-earth - Birzer, Bradley J., 1967- (Wilmington, Del. : ISI Book, 2003)
Explication of the religious symbolism and significance of Tolkien's Middle-earth stories and situation of Tolkien within the Christian humanist tradition represented by Thomas More and T.S. Eliot, Dante and C.S. Lewis.
The Life and Work of J.R.R. Tolkien -- Myth and Sub-creation -- The Created Order -- Heroism -- The Nature of Evil -- Middle-earth and Modernity -- Conclusion: The Nature of Grace Proclaimed.
Includes bibliographical references (p. [177]-203) and index.
Keywords: Tolkien, J. R. R. -- 1892-1973.; Tolkien, J. R. R. -- 1892-1973 -- Religion; Christianity and literature -- England -- History -- 20th century; Christian fiction, English -- History and criticism; Fantasy fiction, English -- History and criticism; Middle Earth (Imaginary place); Good and evil in literature; Myth in literature